Effect of Human Resources Quality, Performance Evaluation, and Incentives on Employee Productivity at Raharja High School - Mulyati; Zebua, Selamat; Chakim, Mochamad Heru Riza; Khairul; Mulyati, Mulyati (Pandawan, 2023)
This study used a sample of 30 employees of Raharja College, Cikokol, Tangerang which were taken randomly to test the effect of the quality of human resources, job evaluation, incentives on employee productivity. The survey method with path analysis technique was used to analyze the pattern of relationships between variables with the aim of knowing the direct or indirect effect of a set of independent variables (exogenous) on the dependent variable (endogenous) with data analysis using the smart PLS 3.0 version software. The results show that the quality of human resources has a positive effect on employee productivity with a path coefficient value of 0.145, the quality of human resources has a positive effect on incentives with a path coefficient value of 0.121, incentives have a positive effect on productivity with a path coefficient value of 0.784, while performance evaluation has no positive effect on employee productivity with a path coefficient value of -0.103. It can be said that all the hypotheses in this study only one that does not have a positive effect while the rest have a positive effect. From the results of the data analysis, it can be seen that the quality of human resources directly affects employee productivity at Raharja College. Thus, the hypothesis which states that the quality of HR has a direct effect on employee productivity is accepted.